Anthocyanins Content in Blueberries (Vaccinium corymbosumL.) in Relation to Freesing Duration - A. Vollmannová; T. Tóth; D. Urminská; Z. Poláková; M. Timoracká; E. Margitanová (Czech Journal of Food Sciences, 2009)
The changes of total anthocyanins (TA) content in fruit of blueberries in relation to freezing duration are the aim of this study. The samples of 21 chosen cultivars obtained from the research breed station were stored in polyethylene bags in freezing box at temperature -18°C. In ethanolic blueberry extracts TA contents were by spectrophotometric method during the time of 6 months at period of 3 months determined. Significant differences of TA content among the observed cultivars were confirmed. The value interval was 615.8-3206.3 mg/kg. The average TA content in 10 very early, resp. early cultivars was 1655.8 mg/kg, in 5 medium early cultivars 1515.6 mg/kg, in 6 medium late, resp. late cultivars 1431.2 mg/kg. During 6 months of blueberries store in the freezing box the average decrease 16.7% of TA content was observed. The average decrease of TA content in very early, resp. early cultivars was 19.6%, in medium early cultivars 16.5% and in medium late, resp. late cultivars 14%.